Chronic disease and sexuality - Gloria Mabel Carrillo González; Beatriz Sánchez Herrera; Lorena Chaparro Díaz (Universidad de Antioquia, 2013)
This study explored the level of production and contents of information available within the global context on the approach of sexuality in individuals with chronic disease (CD). The following main themes were identified: sexuality as a human right and fundamental part of health for individuals with CD, factors present in situations of CD that generate alterations in sexuality, and the models for assessment, measurement, and intervention of the phenomenon. Scientific production is scarce and limited on sexuality during CD, with the most part of said production from recent years.